The Great Proletarian Cultural Revolution, Disruptions to Education, and Returns to Schooling in Urban China - Giles, John; Park, Albert; Wang, Meiyan (World Bank, Washington, DC, 2012)
In determining whether a country's higher education system should be expanded, it is important for policymakers first to determine the extent to which high private returns to post-secondary education are an indication of the scarcity of graduates instead of the high unobserved ability of students who choose to attend post-secondary education. To this end, the paper identifies the returns to schooling in urban China using individual-level variation in educational attainment caused by exogenous city-wide disruptions to education during the Cultural Revolution from 1966 to 1976. For city-cohorts who experienced greater disruptions, children's educational attainment became less correlated with that of their fathers and more influenced by whether their fathers held administrative positions. The analysis calculates returns to college education using data from the China Urban Labor Survey conducted in five large cities in 2001. The results are consistent with the selection of high-ability students into higher education. The analysis also demonstrates that these results are unlikely to be driven by sample selection bias associated with migration, or by alternative pathways through which the Cultural Revolution could have affected adult productivity.